(untitled) (Scientific journal of the Fergana State University, 2024)
In the study of the language system, the principle of linguistic research, now called anthropocentrism, is of great importance. The anthropocentric paradigm is not only the study of language, but as a system of signs, but as an open system based on live communication, it closely analyzes it. It is a set of doctrines related to other systems - society, man, culture, psyche, etc. Without taking into account the human factor, the creator of language, it is absolutely impossible to fully explain the essence of this amazing phenomenon. This article is devoted to the linguistic and cultural description of analogies with zoonym components.